Model-based Representation of Protection Measures as Solution Patterns. (2016) - Kliewe, Daniel; Anacker, Harald; Dumitrescu, Roman; Wegel, Arthur
Abstract: The mechanical engineering industry and related industries are undergoing a massive shift from classic mechanic-centered products to mechatronics. Summarized under the term "Industry 4.0" systems are becoming intelligent, will be able to self-optimize and will communicate with each other through the internet of things. The described push towards greater multichannel integration, for example integration of functions or inherent intelligence, leads to a greater experience for the customer. However, it also leads to new chances that intruders such as product pirates or hackers can exploit. For the effective protection of intelligent technical systems, suitable protection measures have to be found. Simultaneously the increasing complexity of the systems leads to the need for new methods to handle the complexity during the development process. To meet this challenge Model-Based Systems Engineering (MBSE) is well suited. Suitable measures for a preventive system protection have to be considered already in the model-based systems design. The main goal is the seamless integration of the protection measures in modern methods for an interdisciplinary and holistic systems design. Therefore, the protection measures have to be described as model-based Solution Patterns.